2021
DOI: 10.1007/s15010-021-01669-8
|View full text |Cite
|
Sign up to set email alerts
|

Pulmonary function impairment of asymptomatic and persistently symptomatic patients 4 months after COVID-19 according to disease severity

Abstract: Objective Evaluation of pulmonary function impairment after COVID-19 in persistently symptomatic and asymptomatic patients of all disease severities and characterisation of risk factors. Methods Patients with confirmed SARS-CoV-2 infection underwent prospective follow-up with pulmonary function testing and blood gas analysis during steady-state cycle exercise 4 months after acute illness. Pulmonary function impairment (PFI) was defined as reduction below 8… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
39
0
7

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(52 citation statements)
references
References 46 publications
6
39
0
7
Order By: Relevance
“…Sequelae of COVID-19 on respiratory function in non-CF patients have not been clearly described and mainly involve residuals symptoms up to 6 months from hospital discharge [ 27 , 28 ]. The clinical significance of this condition, which was defined as long COVID, is not fully understood; however, advanced age, severe symptoms in the acute phase, pneumonia, acute respiratory distress syndrome and need of mechanical ventilation were identified as main risk factors [ 29 31 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Sequelae of COVID-19 on respiratory function in non-CF patients have not been clearly described and mainly involve residuals symptoms up to 6 months from hospital discharge [ 27 , 28 ]. The clinical significance of this condition, which was defined as long COVID, is not fully understood; however, advanced age, severe symptoms in the acute phase, pneumonia, acute respiratory distress syndrome and need of mechanical ventilation were identified as main risk factors [ 29 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…The clinical significance of this condition, which was defined as long COVID, is not fully understood; however, advanced age, severe symptoms in the acute phase, pneumonia, acute respiratory distress syndrome and need of mechanical ventilation were identified as main risk factors [ 29 31 ]. In addition, post-infection data on non-CF patients showed altered respiratory function [ 27 , 28 ], with impaired carbon monoxide diffusion capacity of the lungs (DLCO) in ~ 40% of the patients, restrictive patterns in ~ 15% and broncho-obstructive syndrome in ~ 7% [ 32 ]. However, these abnormalities could not be directly related to COVID-19 since it is not possible to exclude a pre-existing respiratory involvement, as pre-infection respiratory assessment tests were not available.…”
Section: Discussionmentioning
confidence: 99%
“…Current priorities for research include (i) establishing the prevalence of persistent or chronic SARS-CoV-2 induced CV injury; (ii) elucidating causal mechanisms including the role of immune system, obesity, endotheliopathy, and genetic predispositions; (iii) developing an understanding of CV symptom burden (as part of the long COVID spectrum) and its association with pathology; (iv) developing and refining scalable diagnostic methods with high specificity for COVID-19-associated CV complications (including POTS); (v) identifying novel therapeutic solutions or repurposing old drugs that can protect or reverse COVID-19-associated long-term CV injury; (vi) evaluating the role of vaccination and SARS-CoV-2 variants on cardiac injury; (vii) evaluating the long-term impact of SARS-CoV-2 infection on those with pre-existing cardiac diseases and future risk of heart failure, ischaemic events, and arrhythmias; (viii) evaluating the effects of COVID-19-related autonomic dysfunction on CV homeostasis; and (ix) understanding the impact of long COVID on healthcare costs and on working population. 4 , 230 , 233 A concerning trend observed in recent studies 36 , 19 , 121 , 268 is the marked dissociation seen between symptoms and objective measures of health highlighting the limitations of routine clinical investigations. In this regard, deeper phenotyping efforts including advanced cardiopulmonary imaging (e.g.…”
Section: Research Prioritiesmentioning
confidence: 97%
“… 5 Post-acute COVID symptoms are difficult to treat because the literature has reported varying degrees of abnormality in spirometry (FEV 1 2-20% below LLN) 6 , 7 and diffusing-capacity-of-the-lung for carbon-monoxide (22-88% below LLN) 6 , 7 alongside various CT abnormalities including ground glass opacities (41-89% present), 6 , 7 reticular patterns (0-67% present) 6 , 7 and atelectasis (33% present). 7 A recent study showed that never-hospitalized patients also reported normal or nearly normal pulmonary function tests (6-37% abnormal at 4-month follow-up) 8 and imaging was rarely available in these patients.…”
Section: Introductionmentioning
confidence: 99%